Pengembangan Media Pembelajaran Elektronika Dasar Untuk Memahami Nilai Resistor Berdasarkan Kode Warna 3 Gelang Dan 4 Gelang Bagi Siswa SMK Kelas X Jurusan Teknik Otomasi Industri - Bagus Dwi Cahyono; Irwanto Irwanto; Muhammad Iqbal Nugraha (Departement of Mathematics Education, 2023)
Resistor is an important part of electronics. Selection of the appropriate value in the resistor can optimize the circuit to work properly. Judging from all existing electronic equipment always requires resistors in designing it or in the manufacturing stage. Errors in selecting the value of the resistor can cause the circuit that is made not to work properly. This learning media aims to understand the value of the existing resistor by finding its value based on the resistor color correctly. This program functions to find the value of a resistor by using input in the form of a resistor bracelet color. This learning media program has been successfully created and the results seen work according to the formula or the size of the resistor you want to measure based on the bracelet color code (either 3 or 4 bracelets). . For a description of the color code on the resistors of each bracelet, it can be adjusted according to the formula and theory.